Reciclagem de misturas 100%RAP: investigação de parâmetros para avaliação e dosagem de agentes rejuvenescedores com foco na fadiga - Almeida Júnior, Pedro Orlando Borges de (2022)
The recycling of asphalt pavements is an alternative for the contemporary paving industry as a response to the considerable increase in the price of asphalt materials and the need to promote sustainability and conservation of natural resources. The use of Reclaimed Asphalt Pavement (RAP) in asphalt concrete has become attractive because it promotes economic and environmental gains, mainly by reducing the consumption of virgin asphalt aggregates and binders. The levels of incorporation of the RAP material in new mixtures are limited due to the characteristics of the binder present in the RAP: high stiffness and elasticity with low cohesive property, resulting in mixtures susceptible to thermal and fatigue cracking. To compensate for the high stiffness, rejuvenating agents (ARs) are used, with the optimal concentration or the dosage generally defined based on penetration, softening point or high and low temperature Performance Grade properties. However, these parameters have little or no direct relationship with one of the main failure mechanisms of recycled asphalt mixtures: fatigue damage. Therefore, this research aimed to evaluate the potential of rejuvenating agents to recover fatigue life and define dosage parameters based on this damage mechanism, from the analysis of binders and validations in 100%RAP asphalt mixtures. Different failure definitions, failure criteria and fatigue life prediction equations were evaluated in order to identify which are sensitive to the effects of ageing and rejuvenation in binders and asphalt mixtures. For this, the study is divided into three experimental chapters, exploring two sources of RAP. In the first experimental chapter, the recovery process of RAP binders in the rotary evaporator was implemented and calibrated through rheological and performance analysis and tests. This section showed that the application of tests on binders was assertive to identify the complete evaporation of the solvent without promoting additional ageing in the materials. In contrast, the procedure conducted by the ASTM standard resulted in binders with residual solvent, underestimating the level of stiffness and the level of ageing. RAP binders were used in the second chapter to analyze the effects of ageing, together with laboratory-aged binders and rejuvenation by two commercial ARs (R and S). In general, the effects of ageing are more intense in properties measured at high temperatures than at low and intermediate temperatures, resulting in different dosages of AR according to the domain of analysis of the chosen criterion. The AR contents defined based on 12 fatigue parameters extracted from the LAS test resulted in similar concentrations, with low values of standard deviation and coefficient of variation when determined by the definitions of failure of drop in 50%|G*|, peak C.N and maximum of the C².N.(1-C). The dosage of ARs by fatigue parameters resulted in lower contents when adopting linear viscoelastic (LVE) and damage by permanent deformation parameters. In the last chapter, ten 100%RAP asphalt mixtures with different concentrations of AR R and combination of AR R and HiMA, and two reference mixtures were investigated for the effect of ageing and rejuvenation on LVE and performance properties. The action of AR R and AR R + HiMA resulted in more stiff and less flexible mixtures at high temperatures, and less stiff and more flexible at intermediate and low temperatures when compared to mixtures with virgin materials. Regarding fatigue, the effects of ageing and rejuvenation were identified in the C vs S, in the GR and DR rupture criteria, in analytical solutions of fatigue life simulations and in FlexPAVETM performance. From the correlations between the results of the LAS and the simulations in FlexPAVETM, it was identified that the use of failure definitions of peak C.N and maximum C².N.(1- C), with the prediction of fatigue life by the equation of Wang et al. (2015), resulted in correlations above 0.84 regardless of strain level (2.5% and 5%) and Fatigue Factor Binder - FFB range (1.0% to 2.5%, 2.5 % to 5.0% and 1.0% to 5.0%). Thus, these calculation formulations can be proposed to select and dose the rejuvenating agent based on fatigue damage